High performance of combined HPV testing and genotyping for HPV16/18/52/58 in triaging women with minor cervical cytological abnormalities in northern Thailand. Issue 1 (30th June 2015) - Khunamornpong, Surapan; Settakorn, Jongkolnee; Sukpan, Kornkanok; Srisomboon, Jatupol; Intaraphet, Suthida; Siriaunkgul, Sumalee
Abstract : Human papillomavirus (HPV) infection is an important cause of cervical cancer. Screening with cytology or combined cytology and HPV testing helps to detect early cervical cancers and precancerous lesions (high‐grade squamous intraepithelial lesion or worse [HSIL+]). Minor cytological abnormalities (atypical squamous cells of undetermined significance and low‐grade squamous intraepithelial lesion) account for the majority of abnormal cervical cytology results, but only 10–20% of women with minor cytological abnormalities have histologic HSIL+. Triage tests are useful to identify the high‐risk patients and reduce the colposcopy burden. This study was aimed to evaluate the triage performance of combined HPV DNA testing and genotyping. Cervical samples from women with minor cytological abnormalities, who underwent colposcopy at Chiang Mai University Hospital in northern Thailand between October 2010 and February 2014, were tested for HPV DNA using Hybrid Capture 2 (HC2). Genotyping was performed using Linear Array assay. Of 223 women with cervical histology confirmation, histologic HSIL+ was detected in 25 women (11.2%). The sensitivity, specificity, positive predictive value, and negative predictive value of 3 triage methods for histologic HSIL+ were; 100%, 47.5%, 19.4%, and 100% by HC2 only; 40.0%, 88.4%, 30.3%, and 92.1% by combined HC2 and genotypes HPV16/18; and 96.0%, 75.8%, 33.3%, and 99.3% by combined HC2 and genotypes HPV16/18/52/58. Triage using combined HC2 and genotypes HPV16/18/52/58 showed significantly greater area under the receiver operating curve than the other 2 methods ( P < 0.001). Combined HPV DNA testing and genotyping for HPV16/18/52/58 is useful for triaging women with minor cervical cytological abnormalities in northern Thailand. J. Med. Virol. 88:135–143, 2016 . © 2015 Wiley Periodicals, Inc.